SELF-PERCEPTION AND ATTITUDES OF UFMT STUDENTS REGARDING WEIGHT AND BODY IMAGE - Lopes, Tomires Campos (2022)
Cross-sectional study with the objective of knowing the profile of the risk behavior of undergraduates regarding the condition of the degree of overweight and obesity and how self-measures to maintain the agreed standards. The NCHRBS collection instrument was used with students from the Federal University of Mato Grosso, which had 7,194 completed. The results revealed a sample with a majority of the female sex (F= 4193 - 58.3%; M= 3001 - 41.7), with a mean age of 24.37 years, with prevalence of overweight and obesity, from the areas of Science Social, Health Sciences and Engineering. Students perceive themselves with distortions between what they really have with self-perception of weight, underestimating or overestimating it. Appropriate attitudes to maintain the ideal weight range from the use of diet, exercise to the use of laxatives. The need to establish internal care and monitoring policies for the university population is evident.